Tauberian Remainder Theorems for the Weighted Mean Method of Summability - Sezer, Sefa Anil; Canak, Ibrahim (Mathematical Modelling and Analysis, 2014)
Using the weighted general control modulo, we prove several Tauberian remainder theorems for the weighted mean method of summability. Our results generalize the results proved by Meronen and Tammeraid [Math. Model. Anal. 18 (1) 2013, 97–102].